The Conceptual Approach of Preconceptional Care in Ayurveda - Rajashree Shelare Raut; Praful Raut (International Journal of Ayurveda and Pharma Research, 2022)
For every couple, pregnancy is one of the most beautiful precious events created by nature and it should always be planned not by accidental or chance. The concept of preconception is described in Ayurveda as a Garbhdhanvidhi. It explains about right mode of conception and importance of diet, lifestyle and Shodhan. Preconceptional care plays important role to identify the risk factors, stabilizing the previous disease, to discontinue the teratogenic medications and to prevent any reproductive disease and to ensure that women enters pregnancy with optimal state of health which would be safe for both foetus and herself. The preconception care which may be adopted by all the couples planning for pregnancy. So may be implemented as an integral part in community healthcare. Preconception care begins with the selection of the right partner, which includes right mode of conception and balanced diet, modification of lifestyle and Shodhan Chikitsa which helps to detox and normalize vitiated Dosha that will help to established foundation for the outcome of healthy progeny.Preconceptional care is to identify the risk factors, stabilizing the previous disease, to discontinue the teratogenic medications and to prevent repetitive reproductive disease and to ensure that women enter pregnancy with optimal state of health which would be safe for both foetus and herself.The concepts described in Ayurveda which must be elaborated and studied in details with scientific methods. It is need of an hour to develop the guidelines for preconceptional counseling and it could be completed after research work.